2021
DOI: 10.3389/fpls.2021.620245
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Driven Adaptations of Leaf Cuticular Waxes Are Inheritable for Medicago ruthenica

Abstract: Cuticular waxes covering the plant surface play pivotal roles in helping plants adapt to changing environments. However, it is still not clear whether the responses of plant cuticular waxes to their growing environments are inheritable. We collected seeds of Medicago ruthenica (a perennial legume) populations from 30 growing sites in northern China and examined the variations of leaf cuticular waxes in a common garden experiment. Four wax genes, MrFAR3-1, MrFAR3-2, MrCER1, and MrKCS1, involved in biosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[20] Plants are able to adjust the load and composition of cuticular waxes in accordance with changing environment and abiotic stress conditions, such as temperature fluctuations, drought, radiation level etc. [22] In the recent decades, wax compounds have received growing attention from the standpoint of chemophenetics. Their chemophenetic significance in conifer order Pinales at the familial and subfamilial level has been addressed in detail by Maffei et al [23] Moreover, they are often used as markers in studies on population variability and differentiation of several conifer species.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Plants are able to adjust the load and composition of cuticular waxes in accordance with changing environment and abiotic stress conditions, such as temperature fluctuations, drought, radiation level etc. [22] In the recent decades, wax compounds have received growing attention from the standpoint of chemophenetics. Their chemophenetic significance in conifer order Pinales at the familial and subfamilial level has been addressed in detail by Maffei et al [23] Moreover, they are often used as markers in studies on population variability and differentiation of several conifer species.…”
Section: Introductionmentioning
confidence: 99%
“…The current study marks the initial phase of a broader project focused on genes related to resistance to abiotic and biotic stress, focusing here on cuticle thickness. This aspect is critically important due to cuticle significant influence on resistance to drought, insolation, and pests [66][67][68], as the cuticle is essential for plant survival in periods of severe drought [69] and pests and disease attack [70]. BODYGUARD genes in plants typically encode for proteins that are directly involved in defending the plant against various stresses, including the biosynthesis of cutin in Arabidopsis [69,71,72], mainly the α/β hydrolase protein [69,71,73].…”
Section: Introductionmentioning
confidence: 99%
“…Stress modeling in addition to field and controlled studies have revealed that plants adjust their cuticular wax load and composition to adapt to changing environment and abiotic stress conditions, such as drought, temperature fluctuations, and radiation level ( Shepherd and Griffiths, 2006 ; Guo et al, 2015 , 2021 ; Gao et al, 2016 ). Drought stress has been shown to increase cuticular wax load and the content of alkanes in Arabidopsis ( Kim et al, 2007 ; Kosma et al, 2009 ), while enhanced UV-B radiation was shown to increase the content of alkanes and primary alcohols in cucumber ( Cucumis sativus ) cotyledon ( Fukuda et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%